Hormonal changes of the normal menstrual cycle. - Garmendia, Fausto (2015)
Hormonal variations that characterize the normal menstrual cycle, noting that depends on adequate hypothalamic-pituitary-ovarian interaction are reviewed. He realizes the daily changes of the gonadotropins, estrogens and progesterone, as measured by radioimmunoassay blood analysis, gained over 7 normal menstrual cycles. It was found that the concentrations of FSH and LH are slightly higher in the follicular phase than in the luteal, displaying all mesocíclica them a matching rise in the ovulatory phase of both LH and FSH. Estradiol showed a significant elevation pre-ovulatory surge of gonadotropins and another in the luteal phase. Progesterone remained at a low level during the follicular phase increase substantially since the onset of the ovulatory peak of gonadotropins. The meaning of these hormonal changes is discussed.